Overexpression of CDC7 in malignant salivary gland tumors correlates with tumor differentiation - Jaafari-Ashkavandi,Zohreh (2019)
Abstract Introduction: Cell division cycle-7 protein is a serine/threonine kinase that has a basic role in cell cycle regulation and is a potential prognostic or therapeutic target in some human cancers. Objectives: This study investigated the expression of cell division cycle-7 protein in benign and malignant salivary gland tumors and also its correlation with clinicopathologic factors. Methods: Immunohistochemical expression of cell division cycle-7 was evaluated in 46 cases, including 15 adenoid cystic carcinoma, 12 mucoepidermoid carcinoma, 14 pleomorphic adenoma, and 5 normal salivary glands. Cell division cycle-7 expression rate and intensity were compared statistically. Results: The protein was expressed in almost all tumors. The intensity and mean of cell division cycle-7 expression were higher in malignant tumors in comparison with pleomorphic adenomas (p = 0.000). The protein expression was correlated with tumor grades (p = 0.000). Conclusions: The present study demonstrated cell division cycle-7 overexpression in malignant salivary gland tumors in comparison with pleomorphic adenomas, and also a correlation with tumor differentiation. Therefore, this protein might be a potential prognostic and therapeutic target for salivary gland tumors.